Product Inhibition of Potato Tuber Pyrophosphate:Fructose-6-Phosphate Phosphotransferase by Phosphate and Pyrophosphate - Stitt, Mark (1989)
The product inhibition of potato (Solanum tuberosum) tuber pyrophosphate:fructose-6-phosphate phosphotransferase by inorganic pyrophosphate and inorganic phosphate has been studied. The binding of substrates for the forward (glycolytic) and the reverse (gluconeogenic) reaction is random order, and occurs with only weak competition between the substrate pair fructose-6-phosphate and pyrophosphate, and between the substrate pair fructose-1,6-bisphosphate and phosphate. Pyrophosphate is a powerful inhibitor of the reverse reaction, acting competitively to fructose-1,6-biphosphate and noncompetitively to phosphate. At the concentrations needed for catalysis of the reverse reaction, phosphate inhibits the forward reaction in a largely noncompetitive mode with respect to both fructose-6-phosphate and pyrophosphate. At higher concentrations, phosphate inhibits both the forward and the reverse reaction by decreasing the affinity for fructose-2,6-bisphosphate and thus, for the other three substrates. These results allow a model to be proposed, which describes the interactions between the substrates at the catalytic site. They also suggest the enzyme may be regulated in vivo by changes of the relation between metabolites and phosphate and could act as a means of controlling the cytosolic pyrophosphate concentration.